2012
DOI: 10.1063/1.3694102
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen fluoride adsorption and reaction on the α-Al2O3(0001) surface: A density functional theory study

Abstract: The adsorption and reaction behaviors of HF on the α-Al(2)O(3)(0001) surface are systematically investigated using density functional theory method. By increasing the number of HF molecules in a p(2 × 1) α-Al(2)O(3)(0001) slab, we find that HF is chemically dissociated at low coverage; while both physical and dissociative adsorption occurs at a 3/2 monolayer (ML) coverage. At the same coverage (1.0 ML), diverse configurations of the dissociated HF are obtained in the p(2 × 1) model; while only one is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…From the figure, it can be seen that the electronegative F atom gains electrons that are polarized toward the bound Al atom at the surface and that the H atom forms a covalent bond with a surface oxygen atom ( d O–H = 0.99 Å). The optimized geometry and charge density difference plots are similar to those of one HF adsorbed on the α-Al 2 O 3 (0 0 0 1) surface reported by Quan et al We also performed Bader charge analysis and found that the surface O–H and Al–F have charges of −0.85 and +1.62, respectively. More information about this is given in section S6 of the Supporting Information.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…From the figure, it can be seen that the electronegative F atom gains electrons that are polarized toward the bound Al atom at the surface and that the H atom forms a covalent bond with a surface oxygen atom ( d O–H = 0.99 Å). The optimized geometry and charge density difference plots are similar to those of one HF adsorbed on the α-Al 2 O 3 (0 0 0 1) surface reported by Quan et al We also performed Bader charge analysis and found that the surface O–H and Al–F have charges of −0.85 and +1.62, respectively. More information about this is given in section S6 of the Supporting Information.…”
Section: Resultssupporting
confidence: 81%
“…For example, a first-principles simulation of ALD of alumina on the α-Al 2 O 3 (0 0 0 1) surface has been published . The mechanism of HF adsorption on the α-Al 2 O 3 (0 0 0 1) surface has been studied in detail by Quan et al However, ALD-deposited alumina is found to transform under annealing into θ-Al 2 O 3 , which is the most stable transition phase of alumina. We therefore use θ-Al 2 O 3 as a periodic model for ALD-grown alumina in this study.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…The loss of HF is believed to be the result of surface interactions with the α-alumina reactor tube. Indeed, there is experimental evidence in the literature for HF adsorption under dry conditions on α-alumina. This phenomenon was further observed at temperatures above 550 °C, where it was noted that HF desorption from the α-alumina tube surface started to occur. Consequently, the concentration of SO 2 was used as a proxy for PFOS conversion in the estimation of the rate constant k 1 for the α-alumina tube.…”
Section: Resultsmentioning
confidence: 93%
“…This study also complements previous theoretical and experimental examinations of the fluorination of Al 2 O 3 . Earlier theoretical investigations have studied the fluorination of α-Al 2 O 3 by HF using density functional theory (DFT) methods. , Recent theoretical investigations have also examined the fluorination of Θ-Al 2 O 3 surfaces by HF and compared the fluorination to measured etch rates during Al 2 O 3 ALE . Many experimental studies have also explored the fluorination of Al 2 O 3 because of the effect of fluorination on heterogeneous catalysis. , Fluorination is known to create strong Lewis acid sites that are important in a variety of reactions.…”
Section: Introductionmentioning
confidence: 99%